Antioxidant and xanthine oxidase inhibitory activity of Durio Zibethinus flower (Bangladesh Journal of Botany, 2026)
Durio zibethinus, a well-known plant has garnered scientific interest due to its reported medicinal properties. This study investigated the antioxidant effects of flavonoid-enriched ethanolic extract derived from D. zibethinus flowers, specifically focusing on its ability to inhibit xanthine oxidase in vitro. The D. zibethinus flower ethanolic extract exhibits significant antioxidant effects and xanthine oxidase inhibitory activity, suggesting its promise as a natural therapeutic agent for Gout treatment.Bangladesh J. Bot. 55(1): 161-165, 2026 (March)